Abrigos diurnos, agrupamentos e lesões corporais no morcego hematófago Desmodus rotundus (Chiroptera, Phyllostomidae) do Estado de São Paulo - Rocha, Fabrícia Aparecida da [UNESP] (Universidade Estadual Paulista (Unesp), 2005)
Desmodus rotundus tem sido considerado como uma espécie versátil na ocupação de diferentes tipos de abrigos naturais e artificiais, onde podem formar agrupamentos cuja organização social é estabelecida por interações agonísticas. Essas interações podem envolver apenas “displays”, porém brigas são freqüentes. Esse comportamento agressivo parece ser importante para a propagação de doenças, como a raiva, dentro da colônia. A raiva é uma zoonose letal transmitida através de mordeduras. Acredita-se que uma das formas de evidenciar as agressões em morcegos é analisar suas lesões corporais. Assim, no presente estudo, foram analisados os abrigos diurnos, os tipos de agrupamentos e as lesões corporais em indivíduos de 11 agrupamentos da região de Botucatu e de São João da Boa Vista, Estado de São Paulo. Entre outubro de 2002 e abril de 2003, os morcegos foram capturados em redes armadas defronte aos abrigos e examinados individualmente à procura dessas lesões. Todas as lesões foram consideradas como conseqüência de interações agressivas. No total, foram examinados 258 morcegos, dos quais 67 eram fêmeas e 191 eram machos. As colônias e os agrupamentos de machos solteiros estavam alojados tanto em abrigos diurnos artificiais, como em abrigos naturais, com um leve predomínio dos primeiros. Essas colônias tinham um tamanho médio estimado de 41 indivíduos, enquanto que os agrupamentos de machos solteiros tinham cerca de 26 morcegos. Indivíduos intrusos, quase todos machos, foram... .

Desmodus rotundus has been found to be a versatile species to inhabit different kinds of natural and menmade roosts, where they can group in social organization established by agonistic interactions. These interactions may involve only displays, however fights are often. This aggressive behavior seems to be important to zoonoses propagation inside colony, as rabies. The rabies is a lethal zoonoses transmitted through bites. One of the forms to evidenciate bats aggressions is to analyze corporal lesions. In the present study, were analyzed diurnal roosts, kinds of groupings and corporal lesions on bats from 11 grouping of region of Botucatu and São João da Boa Vista, São Paulo State. Between October 2002 and April 2003, bats were captured using mist nets in front of roosts, and they were examined individually to search for lesions. All lesions were considered as consequence of aggressive interactions. In total, 258 bats were examined, which 67 were females and 191 were males. These colonies and grouping of single males were located both in natural and in menmade roosts, with predominance of natural ones. These colonies had a medium size of 47 individuals, while grouping of single males had about 26 bats. Intruders, almost all males, were captured in the beginning of the night, while they were going into studied roosts. Most of them (67,4%) showed some kind of lesion in the body. These lesions were more frequent in males than in females, even this difference is not statistically significant. From 191 analyzed males, 91,0% showed some kind of lesion, while this proportion was of 70,0% in females. In general, most of males and females, considering all development stages (juveniles and adults) and all reproductive phases, showed some kind of corporal lesion. The more evident differences, even not significant, have occurred in non-pregnant females (76,9%) and in sexual actives... (Complete abstract, click electronic address below).
Keywords: Morcego - São Paulo (Estado)